The Effect Of Standardized Extract Of Eurycoma Longifolia On Phase I And Phase Ii Metabolic Pathways And Rosiglitazone Pharmacokinetics - Purwantiningsih, Purwantiningsih (2013)
The belief that natural products are safer than synthetic drugs has led to the dramatic growth in herbal medicine usage. However, herbal preparations have the potential to cause toxicity, herb-drug interactions and may affect the drug therapeutic effects. Eurycoma longifolia Jack (Tongkat Ali) has been widely used by the local population as an aphrodisiac, and contains many chemical constituents which should be monitored for herb-drug interactions. Therefore, study about the effects of the standardized extract of E. longifolia on the pharmacological profile involving metabolism phase I and II, and the pharmacokinetics of rosiglitazone needs to be conducted to ensure the efficacy and safety of use.